Effect of Ferredoxin Receptor FusA on the Virulence Mechanism of Pseudomonas plecoglossicida - He, Rongchao; Wang, Jiajia; Lin, Miaozhen; Tian, Jing; Wu, Bi; Tan, Xiaohan; Zhou, Jianchuan; Zhang, Jiachen; Yan, Qingpi; Huang, Lixing (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas plecoglossicida is an aerobic Gram-negative bacterium, which is the pathogen of “Visceral white spot disease” in large yellow croaker. P. plecoglossicida is a temperature-dependent bacterial pathogen in fish, which not only reduces the yield of large yellow croaker but also causes continuous transmission of the disease, seriously endangering the healthy development of fisheries. In this study, a mutant strain of fusA was constructed using homologous recombination technology. The results showed that knockout of P. plecoglossicida fusA significantly affected the ability of growth, adhesion, and biofilm formation. Temperature, pH, H2O2, heavy metals, and the iron-chelating agent were used to treat the wild type of P. plecoglossicida; the results showed that the expression of fusA was significantly reduced at 4°C, 12°C, and 37°C. The expression of fusA was significantly increased at pH 4 and 5. Cu2+ has a significant inducing effect on the expression of fusA, but Pb2+ has no obvious effect; the expression of fusA was significantly upregulated under different concentrations of H2O2. The expression of the fusA gene was significantly upregulated in the 0.5 4-μmol/l iron-chelating agent. The expression level of the fusA gene was significantly upregulated after the logarithmic phase. It was suggested that fusA included in the TBDR family not only was involved in the transport of ferredoxin but also played important roles in the pathogenicity and environment adaptation of P. plecoglossicida.